Malaysian souvenirs and tourists' behaviour toward authenticity as an important souvenir attribute - Abdullah @ Zawawi, Muhammad Irfan (2012)
The purpose of this study is to evaluate the role of authenticity, as an important factor in the souvenir purchase behaviour of Malaysia’s international tourists. Demographic characteristics (gender, age, origin and annual income) have major influence on the preference of souvenir categories and importance of souvenir attributes. The three most preferred souvenir categories among international tourist are respectively “clothing & accessories”, “food, drink & chocolates” and “handicraft”. The authenticity attribute ranked second among most important factors following physical attributes in the souvenir purchase behaviour of Malaysia’s international tourists. The survey result shows international tourists tend to find traditional & cultural meaning and Malaysian made product, as the most important souvenir authenticity attributes. 85% of survey tourists’ respondents are willing to pay more for local made souvenirs made compare to the imported products. According to the results of Pearson correlation tests, older tourists have higher tendency to purchase local made souvenirs compare to younger tourists. Cross tabulation tests shows tourists from Europe, America, Africa and Oceania are more concerned about authenticity attributes compare to Asian and Middle Eastern respondents who are more concerned about Aesthetic Attributes and Value Attributes. Majority of international tourists are relatively satisfied with the Malaysian souvenir market.